Functional connectivity study on visually evoked auditory response based on high-density electroencephalography - Jia, Ning; Feng, Yueting; Han, Kun (Frontiers in Neuroscience, 2026)
AimThis study aimed to investigate the brain activity involved in visually evoked auditory response (vEAR) using high-density electroencephalography (EEG) and explore the differences in connections between visual and auditory cortex.MethodsThirty-seven subjects with vEAR and Thirty four subjects without vEAR, matched by age and gender, were recruited. The hearing threshold, years of education, and the Trail Making Test (versions A and B) results were collected from all patients. All participants underwent a 256-channel EEG, and neurophysiological differences were evaluated using standardized low-resolution brain electromagnetic tomography (sLORETA).ResultsTrail Making Test scores in vEAR group were 17.3 ± 2.70 s and 26.28 ± 3.83 s for versions A and B, respectively, and 20.13 ± 6.88 s and 46.65 ± 5.971 s, respectively, in non-vEAR group. Significant difference in version B score was observed between two groups. Compared with non-vEAR group, significant differences were observed at the delta (p = 0.005), theta (p = 0.016), alpha1 (p = 0.016), alpha2 (p = 0.011), beta3 (p = 0.024), and gamma (p = 0.048) frequency bands in vEAR group. In addition, vEAR group showed significantly reduced activation of the posterior cingulate cortex (BA31, p = 0.0306) at the alpha2 frequency band and the insular cortex (BA13, p = 0.0306) at the beta2 frequency band. Moreover, significantly increased synchronized beta3 connectivity was found between the right part of the cingulate cortex (BA30) and the right primary auditory cortex (BA41) in vEAR group (p = 0.045).ConclusionvEAR group showed stronger regional connection characteristics than non-vEAR group, which may represent a neural signature associated with vEAR.